Guillain-Barré syndrome: a review of immunotherapy, rehabilitation, and long-term outcomes - Ali, Bayan M.; Alghamdi, Ahmed A.; Alanazi, Wadha R.; Alsamti, Asma A.; Allahyani, Abdulaziz F.; Altalhi, Mohammed M.; Alghamdi, Ali A.; Alareef, Shubaily F.; Alsedrah, Ali H.; Algarbo, Mosaed S.; Alshehri, Mohammed A. (International Journal Of Community Medicine And Public Health, 2023)
Guillain-Barré syndrome (GBS) is a complex autoimmune disorder characterized by the rapid onset of motor weakness and sensory disturbances, often precipitated by preceding infections. GBS is considered a rare disorder, with an estimated annual incidence ranging from 0.6 to 4.0 cases per 100,000 individuals. It constitutes a medical emergency due to its potential for severe disability or mortality. The hallmark clinical features of GBS include progressive symmetric muscle weakness and sensory disturbances. Diagnosis relies on clinical evaluation, cerebrospinal fluid analysis, and electrodiagnostic studies, with the Brighton criteria providing standardized diagnostic criteria. The hallmark clinical features include progressive symmetric muscle weakness, sensory deficits, and areflexia or hyporeflexia. The management of GBS primarily involves supportive care and immunomodulatory therapies. Plasmapheresis, or plasma exchange, and intravenous immunoglobulin (IVIG) are the mainstay treatments aimed at modulating the immune response and shortening the illness duration. Rehabilitation, encompassing physical and occupational therapy, is pivotal for restoring functionality and improving long-term outcomes.